The Influence of Intellectual Intelligence and Work Commitment on Employee Performance: The Moderating Role of Work Motivation at CV. Riau Jaya Abadi Medan - Fenny Chandra; Michael Michael (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examines the influence of intellectual intelligence and work commitment on employee performance at CV. Riau Jaya Abadi Medan, with work motivation serving as a moderating variable. A non-probability sampling method was employed, with data collected through a census of 80 employees from the technical or mechanical departments. The study utilized questionnaires to measure intellectual intelligence, work commitment, work motivation, and employee performance. Data were analyzed using SPSS version 20, employing validity and reliability testing, descriptive statistics, normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression, correlation analysis, partial (t-test), moderation, and simultaneous (F-test) analyses. The descriptive findings indicate that intellectual intelligence is categorized as low, while work commitment and motivation are considered moderately good, and employee performance is rated as good. The partial test results reveal that both intellectual intelligence and work commitment have positive and significant effects on employee performance. Furthermore, the moderation analysis shows that work motivation strengthens the effects of both intellectual intelligence and work commitment on employee performance. The adjusted R² value of 0.554 indicates that 55.4% of employee performance variation is explained by intellectual intelligence and work commitment, while the remaining 44.6% is influenced by other variables such as work environment, organizational culture, and work discipline.